Robotic Cardiac Surgery - Gao, Changqing; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
Robotic Cardiac Surgery is a comprehensive guide to robotic/totally endoscopic cardiac surgery. The book is intended to provide in-depth information regarding the history of robotic surgical systems, their components and principles. It emphasizes patient selection, perioperative management, anesthesia considerations and management, operative techniques and management, postoperative care and results. Extensive, detailed photographs and illustrations of different kinds of robotic surgery are also included. It provides cardiac surgeons, cardiac anesthesiologists, and perfusionists with a comprehensive review of current robotic cardiac surgeries and related knowledge. Changqing Gao, MD, is a professor at the Department of Cardiovascular Surgery, PLA General Hospital, Beijing, China.
Overview of Robotic Cardiac Surgery -- Anesthesia for Robotic Cardiac Surgery -- Intraoperative Transesophageal Echocardiography in Robotic Cardiac Surgery -- Peripheral Cardiopulmonary Bypass Establishment for Robotic Cardiac Surgery -- Robotic Surgery in Congenital Heart Diseases -- Totally Robotic Myxoma Excision -- Robotic Mitral Valve Surgery -- Robotic Coronary Bypass Graft on Beating Heart -- Hybrid Coronary Revascularization -- Robotic Left Ventricular Epicardial Lead Implantation.
Keywords: Medicine; Surgery; Heart -- Surgery; Endoscopic surgery; Medicine & Public Health; Cardiac Surgery; Minimally Invasive Surgery; Surgery